The Status of Farmers' Co-Operative Associations under Federal Law - Jones, Franklin D. (Journal of Political Economy, 1921)
From the beginning of federal regulation of combination there has been an insistent demand on the part of the farmers for the exemption of their organizations. The political history of the past thirty years is full of party promises to the farmers, but the laws on the statute books reveal a rather niggardly performance of the promises made.